Unraveling the HIV-malaria interactions: a bibliometric analysis of global research trends and emerging insights - Zhang, Huize; Chen, Guoren; Ma, Ping; Lai, Yu (Frontiers in Microbiology, 2025)
BackgroundThe co-infection of human immunodeficiency virus (HIV) and malaria has emerged as an urgent public health challenge in tropical areas where the two diseases geographically converge, stimulating extensive biomedical investigations into their pathobiological interactions. This study aims to elucidate the current status and research trends regarding the interactions between HIV and malaria through bibliometric and visualized analysis.MethodsResearch on the interactions between HIV and malaria was collected from the Web of Science Core Collection. Bibliometric analysis and knowledge graph visualization were performed on 4,717 articles published between 1995 and 2024, using CiteSpace software.ResultsThe results demonstrate a fluctuating upward pattern in the number of publications related to HIV and malaria interactions. According to the cooperative network visualization analysis, the United States, the University of London, and Grant Dorsey possess the greatest publication counts among all countries, institutions, and authors, respectively. The keyword and cocited reference analysis distinguish the primary research hotspots and frontiers as the epidemiological study of different populations in the African region, pathogenic mechanisms underlying HIV-malaria co-infection, strategies for the prevention and treatment of HIV and malaria co-infection, interactions between antimalarial and antiretroviral drugs, and malaria vaccine responses in HIV-infected individuals.ConclusionThis bibliometric investigation outlines the research hotspots, frontiers, and trends regarding the interactions between HIV and malaria. Future research should delineate pharmacokinetic and pharmacodynamic interactions between antimalarial and antiretroviral drugs to enhance clinical efficacy and medication safety and develop effective malaria vaccines that benefit HIV-positive populations in endemic areas.